2022
DOI: 10.1002/jcv2.12080
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review investigating the use of exposure for the treatment and targeted prevention of anxiety and related disorders in young people

Abstract: BackgroundCognitive Behavioural Therapy (CBT) is the gold standard intervention for anxiety and related mental health disorders among young people; however, the efficacy of individual elements of CBT (e.g., exposure to feared stimuli) have received little scrutiny.AimsThis scoping review, informed by three stakeholder groups and a scientific advisory group, aimed to identify the nature and extent of the available research literature on the efficacy of exposure to feared stimuli, moderators of effectiveness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The game presents a wide range of situations that require adaptation to changing environments, and generation of effective answers in contexts where time is limited (Vlachopoulos and Makri, 2017). In addition, other researchers have reported that prolonged exposure facilitates experimentation with multiple strategies when solving problems, which also strengthens this skill (Donkin and Rasmussen, 2021;Teunisse et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The game presents a wide range of situations that require adaptation to changing environments, and generation of effective answers in contexts where time is limited (Vlachopoulos and Makri, 2017). In addition, other researchers have reported that prolonged exposure facilitates experimentation with multiple strategies when solving problems, which also strengthens this skill (Donkin and Rasmussen, 2021;Teunisse et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…JCPP Advances also requires authors to adhere to the PRISMA guideline in the reporting of systematic reviews. The June issue of JCPP Advances have included three high quality systematic reviews covering important research questions related to (i) structural and functional brain changes associated with peer‐victimisation, bullying, and cyberbullying (Ke et al., 2022 ), (ii) the associations between adverse experiences and mental health outcomes in individuals with minority identities related to sexual orientation, gender expression, or gender identity (Jonas et al., 2022 ), and (iii) the use of exposure in the management of anxiety‐related disorders among young people (Teunisse et al., 2022 ). As expected from publications in JCPP Advances, the above mentioned systematic reviews all followed PRISMA guidelines.…”
Section: Reporting Guidelinesmentioning
confidence: 99%